Hermeneutics Controvercies in Contemporary Islamic Studies - Nurkhalis, Nurkhalis; Fauzan, Fauzan (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
Hermeneutics has changed the paradigm of the study of contemporary Islamic thought towards the direction of Islamic science, placing modern Islamic issues into the discourse of theodiplomacy. Many modernist scholars have initiated an overhaul of the concept of